Karakteristik dan Preferensi Habitat Penyu dalam Membuat Sarang Alami untuk Peneluran - Winarto Winarto; Siva Devi Azahra (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to examine the characteristics and environmental factors of turtles' preferences in making their natural nests. The method used is the descriptive quantitative method. The results showed that there were two types of turtles found during the observation, namely the green turtle (Chelonia mydas) and the hawksbill turtle (Eretmochelys imbricata). Measurements and observations of the characteristics of the 14 nesting points showed that the diameter and depth of the green turtle's nest were larger than those of the hawksbill turtle. Both types of turtles have a preference for nesting areas on sloping beaches with temperatures of 28-30ºC and humidity of 76-89%, as well as being around vegetation in the form of sea pine (Casuarina equisetifolia), sea oyster (Gynura sp), sea pandanus (Pandanus odorifer), sea kangkung (Ipomea peltate) and sea hibiscus (Thespesia populnea). In conclusion, temperature, humidity and types of vegetation around the nest determine the turtle's preference in making natural nests for laying eggs. Keywords: Nest Characteristics, Conservation, Turtle, Habitat Preference